2019
DOI: 10.1101/2019.12.19.883157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning steers the ontogeny of an efficient hunting sequence in zebrafish larvae

Abstract: The success of goal-directed behaviours relies on the coordinated execution of a sequence of component actions. In young animals, such sequences may be poorly coordinated, but with age and experience, behaviour progressively adapts to efficiently exploit the animal's ecological niche. How experience impinges on the developing neural circuits of behaviour is an open question. As a model system, larval zebrafish (Danio rerio) hold enormous potential for studying both the development of behaviour and the underlyi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Thus, experience of live prey may contribute to the ontogeny of prey capture behavior, where older (and therefore more "experienced") fish have more fluid capture maneuvers and hunt prey from a wider angular range [51]. Our finding is consistent with a recent study [52], which showed that differences in hunting kinematics result in higher hunting efficiency in experienced fish.…”
Section: Experience Of Live Prey Improves Hunting Success In Larval Zsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, experience of live prey may contribute to the ontogeny of prey capture behavior, where older (and therefore more "experienced") fish have more fluid capture maneuvers and hunt prey from a wider angular range [51]. Our finding is consistent with a recent study [52], which showed that differences in hunting kinematics result in higher hunting efficiency in experienced fish.…”
Section: Experience Of Live Prey Improves Hunting Success In Larval Zsupporting
confidence: 90%
“…Thus, the prey-capture circuit is hard-wired in the novice hunter's brain. Nonetheless, experience of live prey may shape the circuit as shown in this work and the work mentioned above [52], and as it appears to do in juvenile fish raised in the dark who learn to forage using their lateral line system [56].…”
Section: Experience Of Live Prey Improves Hunting Success In Larval Zmentioning
confidence: 63%